Disrespect and abuse in maternity care in a low-resource setting in Tanzania: Provider’s perspectives of practice - Loveluck K. Mwasha; Lucy M. Kisaka; Eunice S. Pallangyo (PLoS ONE, 2023)
Background Globally, women experience disrespectful and abusive care from maternity healthcare providers at health facilities, committed intentionally or unintentionally, particularly during labor and delivery. Disrespectful care affects women’s childbirth experience and birth outcomes. Methods This study used a descriptive qualitative design to obtain thick and rich data on disrespect and abuse in maternity care in a low-resource setting in Tanzania. Three days workshop was conducted at the Aga Khan University comprising maternity healthcare providers from diverse settings. The workshop was designed based on the existing evidence and anecdotal data and inspired by the authors’ experiences of disrespectful and abusive care (stereotyping clients, not listening to client’s/relatives’ concerns, unconsented care) as a client, relative, or observant of colleagues. The targeted audience was maternity healthcare providers from public and private health facilities in the Dar es Salaam region. Data collection encompassed individual responses (reflection of practice) obtained by individuals, anonymously written reflections of practice, and compiled notes from group discussions. Data were analysed thematically guided by six steps described by Braun and Clerk. Results A total of 80 maternity healthcare providers participated in the workshop from various health facilities, including dispensaries (n = 25), health centres (n = 2), and hospitals (n = 3) located in semi-urban Dar es Salaam. Four main themes were identified from the data: Physical and verbal abuse; Lack of professional ethics and integrity; Vulnerable working environment; Abuse and disrespect to care providers. In addition, several sub-themes were identified within these themes: Harsh and abusive language; Beating/slapping/pinching of the mother in labor; notably, Junior midwives also disrespected and abused women; Lack of privacy and confidentiality; Poor communication; No consent for maternity healthcare procedures; Lack of courtesy and poor interpersonal skills; and, negligence of care and woman’s needs. Conclusion The actions of disrespect and abuse are alarming in practice and are associated with ignorance of fundamental human rights by both providers and recipients of services. Conducting workshops seems a useful approach to revealing disrespect and abuse deep-rooted in practice and provides an opportunity to rectify the problem with providers. A more extensive interventional study will be crucial to address the widespread actions of disrespect and abuse.